Enhance Artificial Intelligence Literacy for Islamic Boarding School Students Using the Asset Based Community Development Method - Heribertus Ary Setyadi; Candra Agustina; Wawan Haryanto; Rousyati Rousyati (STIE AUB Surakarta, 2025)
Use of artificial intelligence (AI) in teaching and learning has become an increasingly important topic in modern education context. AI offers a wide range of potential to enhance students' learning experiences through better personalization and adaptation to individual needs. From initial observations in several Islamic boarding schools in Banjarsari Surakarta, it was found that understanding of students and teachers about AI and AI supporting applications was still lacking. As part of efforts to improve education quality and community readiness to face a digital era, Bina Sarana Informatika University, Surakarta City Campus, took an initiative to implement a community service program in form of training on using AI in education for students. Community service method used in this activity is the Asset Based Community Development (ABCD) approach which aims to empower communities by utilizing existing potential and resources. Implementation stages include needs analysis (Discovery), expectations formulation (Dream), design of training modules (Design), finalization of plans with FGD (Define), and training implementation (Destiny). AI workshop for Islamic boarding schools has been successfully implemented with good results. From questionnaires that have been filled out by all participants, it shows that workshop materials presented are very useful, materials and tutors delivery method are satisfactory. Workshop participants who are satisfied or rate it good are 63% and those who rate it as very satisfied or very good are 32%.